ANALISA KONFLIK EKSEKUTIF â LEGISLATIF KABUPATEN BANYUMAS PERIODE 2008-2013 - , SUKMAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aims of the research is to study political conflict between the government and parliament in the regency of Banyumas in 2009-2013. Since elected at the Pilkada 2008to the end of his tenure, Mr. Mardjoko had always been involved in the conflict with the parliaments. The conflict ranged from his disagreement against the party promoted him to his opposition to the parliament. The conflict intense is controling and budgeting of legislatives to executives. There were two intense conflicts found during his authority namely, controlling parliament about the failure of Bioetanol project in 2008 and budgeting parliament about the delay of pronouncement of APBD 2011 for political partyâs funding. These conflicts occurred due to institutional and non-institutional factors. The institutional factors occurred because (1) the application of direct election of the executives and legislatives which led to the equal position of the parliament and the government